Sol-Gel Synthesis of Zn Doped MgO Nanoparticles and Their Applications. Issue 205 (12th February 2020) - Sharma, Asha; Arya, Sandeep; Singh, Bikram; Prerna,; Tomar, Amit; Singh, Suram; Sharma, Rakesh
Abstract: The physicochemical properties of metal oxide nanoparticles can be significantly improved by doping. MgO and Zn 2+ doped MgO (Zn:MgO) offers potential applications in photonic devices falling in the UV and visible region. In the present paper, sol gel method was employed to synthesize pure and Zn 2+ doped MgO nanoparticles. XRD pattern inferred the crystalline nature of material and also the slight change in peak due to the dopant. FESEM showed the formation of nanoparticles with almost same shapes and dimensions with little agglomeration. Optical properties were studied by using UV-Vis and PL techniques. Doping of Zn 2+ in MgO nanoparticles was verified by EDS.